Metabolomic and transcriptomic changes in mungbean (Vigna radiata (L.) R. Wilczek) sprouts under salinity stress - Lim, Insu; Kang, Minseo; Kim, Byeong Cheol; Ha, Jungmin (Frontiers in Plant Science, 2022)
Mungbean (Vigna radiata) sprouts are consumed globally as a healthy food with high nutritional values, having antioxidant and anticancer capacity. Under mild salinity stress, plants accumulate more secondary metabolites to alleviate oxidative stress. In this study, metabolomic and transcriptomic changes in mungbean sprouts were identified using a reference cultivar, sunhwa, to understand the regulatory mechanisms of secondary metabolites in response to salinity stress. Under salinity conditions, the contents of phenylpropanoid-derived metabolites, including catechin, chlorogenic acid, isovitexin, p-coumaric acid, syringic acid, ferulic acid, and vitexin, significantly increased. Through RNA sequencing, 728 differentially expressed genes (DEGs) were identified and 20 DEGs were detected in phenylpropanoid and flavonoid biosynthetic pathways. Among them, 11 DEGs encoding key enzymes involved in the biosynthesis of the secondary metabolites that increased after NaCl treatment were significantly upregulated, including dihydroflavonol 4-reductase (log2FC 1.46), caffeoyl-CoA O-methyltransferase (1.38), chalcone synthase (1.15), and chalcone isomerase (1.19). Transcription factor families, such as MYB, WRKY, and bHLH, were also identified as upregulated DEGs, which play a crucial role in stress responses in plants. Furthermore, this study showed that mild salinity stress can increase the contents of phenylpropanoids and flavonoids in mungbean sprouts through transcriptional regulation of the key enzymes involved in the biosynthetic pathways. Overall, these findings will provide valuable information for molecular breeders and scientists interested in improving the nutritional quality of sprout vegetables.